Antibacterial activity of dialkyl-aginate biosurfactant cream againts Staphylococcus aureus an Pseudomonas aerugynosa - Kintoko Kintoko; Nining Sugihartini; Benazir Evita Rukaya (Universitas Ahmad Dahlan, 2018)
Dialkyl-alginate biosurfactant is an amphifilik rhamnolipid biosurfactant that has the potential to be developed into an antibacterial agent. The purpose of this study was to prove that the biosurfactant of dialkyl alginate both before and after creams has antibacterial activity especially against Staphylococcus aureus and Pseudomonas aeruginosa. Test of antibacterial activity of biosurfactant dialkyl alginate at concentrations of 5%, 10% and 20% to Staphylococcus aureus and Pseudomonas aeruginosa using Hammond, et al (2011) modified quantitative method. EnbaticÂ® 1% is used as a positive control and sterile aquadest as a negative control. Determination of antibacterial activity of dialkyl alginate biosurfactant followed by analysis of leakage of protein and nucleic acids using UV-vis Spectrophotometry and leakage of Ca2 + and K + metal ions using Atomic Absorption Spetrophotometry (AAS). The most active concentration was formulated into cream and then performed physical evaluation (organoleptic, pH, adhesion, spreading and viscosity) and tested antibacterial activity using the well method. The test results showed that the biosurfactants of dialkyl-alginate before and after the cream was treated as antibacterial activity. The concentration of 10% was the most active concentration having activity which did not differ significantly to positive control with p value of 0,05